Development of the Belarusian Economy: Possibilities and Limitations. Issue 6 (2nd June 2016) - Shirov, A.A.; Sabchishina, K.E.; Potapenko, V.V.
Abstract : At the moment there is no consensus among experts regarding how effective the economic policy of the Republic of Belarus has been in recent years. Assessments of medium- and long-term prospects for its economic development are even less clear. We attempt to express our opinion on these issues. We should first note that the results of Belarus's economic policy will primarily be viewed in comparison with those of the other two largest post-Soviet countries: Russia and Ukraine. This seems to be a natural comparison, considering that in the early 1990s these countries had approximately equal development characteristics and production efficiency parameters.